The Urgency of Public Attitudes of Online Session Rules Implementation in Criminal Cases during COVID-19 Pandemic - Nikmah Fitriah; Muhammad Arief Wijaksono; Maulida Rahmah (Syntax Corporation Indonesia, 2022)
The background of the research entitled